Locoregional interventional therapy for hepatocellular carcinoma: radiologic and clinical factors predictive of untreatable progression and time to untreatable progression - He, Zijun; Zhang, Xueying; Zhang, Yucong; Kong, Jian (Frontiers in Pharmacology, 2024)
Objective: In this retrospective cohort study, we examined independent risk factors that influence untreatable progression (UP) and time to UP (TTUP) in patients with hepatocellular carcinoma (HCC) after locoregional interventional therapy. We evaluated the effects of initial objective response and best objective response on UP occurrence and TTUP after locoregional interventional therapy. Methods: Data were collected from HCC patients initially treated with the drug-eluting beads transcatheter arterial chemoembolization (DEB-TACE) procedure at our hospital from January 2017 to December 2022. Modified response evaluation criteria in solid tumors (m-RECIST) was used to evaluate the radiologic response of tumors. Logistic regression analysis was used to analyze the risk factors for UP in patients and Cox regression analysis was used to discover independent variables that influenced TTUP. Results: In all, 93 patients initially treated with DEB-TACE procedure were included. Subsequent to initial treatment, 50 patients continued with DEB-TACE treatment while 43 received DEB-TACE and sequential thermal ablation treatment. The probability of developing UP was 82.8% (n=77). Furthermore, 49 (52.7%) patients achieved initial objective response and 70 (75.3%) achieved best response. Multivariate logistic regression analysis confirmed three independent risk factors of UP, namely age (OR:0.950, P=0.044); initial objective response (OR:0.177, P=0.020); and treatment regimen (OR:7.133, P=0.007). Multivariate Cox regression found that total bilirubin (HR:1.029, P=0.002); tumor distribution (HR:1.752, P=0.034); Subjective Angiographic Chemoembolization Endpoint (SACE) classification (HR:0.668, P=0.043); number of tumors (HR:1.130, P=0.004); initial objective response (HR:0.539, P=0.019); and treatment regimen (HR:4.615, P<0.001) were independent variables that influenced TTUP. Conclusions: Age, initial objective response, and treatment regimen significantly affected the occurrence of UP in HCC patients. Initial objective response, SACE classification, treatment regimen, total bilirubin, number of tumors, and tumor distribution were significantly correlated with TTUP. The initial objective response after locoregional interventional therapy had greater effects on UP occurrence and TTUP than the best objective response.